Effect of Volatile Compounds Emitted by an Endophytic Yeast Isolated from the Endemic Plant Echinopsis Chiloensis Against Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P; Parada-Fuentes, R; Navarro-Gajardo, F; Navarro-Gajardo, F; Vidal-Águila, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Our research group isolated an endophyte yeast from the endemic plant Echinopsis chiloensis. This yeast, identified as Naganishia sp, produces volatile organic compounds (VOC) with antifungal activity against Botrytis cinerea. Due to the need for alternative control methods for this pathogen, the effect of VOC on B. cinerea was analyzed. On the fourth day of cultivation, in the presence of VOCs, the mycelial growth of B. cinerea stopped. VOCs inhibited 32.8% of the conidia germination and reduced sporulation by 70.6%. These compounds promoted the formation of infection cushions. VOCs caused damage to the cell wall and plasma membrane in B. cinerea. On the other hand, the volatile compounds induced oxidative stress, and led to membrane lipid peroxidation after 16 and 24 h of incubation in the presence of VOCs, because an increased level of malondialdehyde content was observed. These compounds exerted a fungistatic effect on B. cinerea. The volatile compounds emitted by Naganishia sp were identified by gas chromatography coupled with mass spectrometry as 3-methylbutyl acetate, ethylbenzene, 1-ethyl-3-methylbenzene, 2-phenylethanol, 2-heptanone and (5E)-6,10-dimethylundeca-5,9-dien-2-one. The most abundant volatile compound, 2-phenylethanol, inhibited the mycelial growth of B. cinerea with an IC50 value of 0.21 µL mL−1. The effect of this pure compound was also fungistatic. Finally, it was shown that volatile compounds decreased the severity of B. cinerea infection in tomatoes and grapes by 64.7 and 43,1%, respectively. This is the first report identifying volatile compounds emitted by a Naganishia sp. and describing their mode of action against B. cinerea. © 2024 by the authors.